2016
DOI: 10.3390/w8100450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiation Components in a Global Freshwater Model with Station-Based Observations

Abstract: Abstract:In many hydrological models, the amount of evapotranspired water is calculated using the potential evapotranspiration (PET) approach. The main driver of several PET approaches is net radiation, whose downward components are usually obtained from meteorological input data, whereas the upward components are calculated by the model itself. Thus, uncertainties can be large due to both the input data and model assumptions. In this study, we compare the radiation components of the WaterGAP Global Hydrology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 52 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…Similarly to climate models, reanalyses were shown to have difficulties in representing the multidecadal variations in surface shortwave radiation seen in the GEBA data (Wild and Schmucki, 2011). The quality of reanalysis-calculated surface radiative fluxes has also been assessed with GEBA data to check their suitability as input data in a global hydrological modeling framework (Müller Schmied et al, 2016).…”
Section: Validation Of Surface Energy Fluxes From Climate Models Reamentioning
confidence: 99%
“…Similarly to climate models, reanalyses were shown to have difficulties in representing the multidecadal variations in surface shortwave radiation seen in the GEBA data (Wild and Schmucki, 2011). The quality of reanalysis-calculated surface radiative fluxes has also been assessed with GEBA data to check their suitability as input data in a global hydrological modeling framework (Müller Schmied et al, 2016).…”
Section: Validation Of Surface Energy Fluxes From Climate Models Reamentioning
confidence: 99%
“…It is expected to find high correlations from TWSA-SWEA rela- In a number of studies, the performance of the WGHM in the simulation of discharge, reservoir, radiation, and evapotranspiration was evaluated, and it was found that the model estimate in the gridded and basin scales generally outperforms other global models (Masaki et al, 2017;Müller Schmied et al, 2016b;Veldkamp et al, 2018;Wartenburger et al, 2018;Zaherpour et al, 2018Zaherpour et al, , 2019Zhao et al, 2017). The comparison of seasonal amplitudes of the model to GRACE data showed that WGHM underestimates TWSA in the Southern Hemisphere and the tropics but compares favourably with GRACE in the Northern…”
Section: Discussionmentioning
confidence: 99%
“…The Water-Global Assessment and Prognosis Global Hydrology Model (WGHM) is part of the Water-Global Assessment and Prognosis (WaterGAP) model Müller Schmied et al, 2016aMüller Schmied, 2017;Müller Schmied et al, 2016b). It calculates water fluxes and storages on global land area.…”
Section: Wghm Terrestrial Water Storagementioning
confidence: 99%
“…As part of so-called climate or meteorological forcing datasets such as those generated within the Global Soil Wetness Project (GSWP; Zhao and Dirmeyer, 2003), at Princeton University (Sheffield et al, 2006), and within the Integrated Project Water and Global Change (WATCH; Weedon et al, 2011), the longwave and shortwave components of surface downwelling radiation (abbreviated as rlds and rsds or just longwave and shortwave radiation in the following) are used to correct model biases in climate model output (Hempel et al, 2013;Iizumi et al, 2017;Cannon, 2017) and drive simulations of climate impacts, for example (Müller Schmied et al, 2016;Veldkamp et al, 2017;Chang et al, 2017;Krysanova and Hattermann, 2017;Ito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%